Implementasi Pendidikan Karakter Pada Program Kesetaraan Paket A di PKBM Lingkar Lontara Kota Makassar - Iin Masita; Rudi Amir; Muhammad Asri (Universitas Negeri Makassar, 2023)
The purpose of this study is so that researchers are able to achieve a deep understanding of how to implement the Implementation of Character Education. This study uses qualitative research with a case study approach. Data collection techniquesta donenamely Observation, Interview and Documentation with seven informants. The results showed that implements character education by Providing exemplary among school members such as the institution exemplifies good behavior. Involve all Stakeholders such as tutors involved in deliberations. Building and Complying with School Norms, Rules and Traditions such as providing order. Developing School Branding by providing adequate facilities and infrastructure. Developing Literacy Activities by providing reading programs.